Peranan Pemerintah Daerah Dalam Pengentasan Kemiskinan Di Desa Huidu Kecamatan Limboto Barat Kabupaten Gorontalo - Sarfan Tabo; Arpin; Nursafitra M; Ahiar Biongan (Journal Governance and Politics (JGP), 2022)
The role of the government bureaucracy has a position in poverty alleviation through programs that have been planned. The role of the government down to the village/kelurahan level which has direct health insurance as the element in charge, executor and companion, must be able to stimulate the growth of community creativity and motivation. Local government according to Feelel heady (1971) is: a phenomenon associated with large scale organizations, the identity of local government as a form of social organization that has certain characteristics. Bureaucracy in organizational terms has the characteristics of a hierarchy of power, specialization and division of labor. Characteristics of bureaucratic behavior in the structure is the result of a pattern of behavior or bureaucracy. The research that was compiled was qualitative in nature. According to (Bogdan and Biklen in Muktar and Widodo 1982) data analysis is the process of systematically searching for and organizing interview transcripts, field notes and other materials found in the field. All that is collected to increase understanding (of a phenomenon) and help to present research findings to others. The role of the local government in alleviating poverty in Huidu village, West Limboto sub-district, needs to be optimized because the success of an activity is greatly influenced by the accuracy of the organization and the quality of education of village officials as well as the seriousness in carrying out the development program, the work system carried out and the supporting elements, namely the quality of the people and the facilities. required. In such circumstances, it will be possible to achieve an efficient and effective governance and development even though the resources are very limited Key Words: Role, Local Government, Alleviation, Poverty